Environmental risks in the developing world: exposure indicators for evaluating interventions, programmes, and policies. Issue 1 (14th December 2004) - Ezzati, Majid; Utzinger, Jürg; Cairncross, Sandy; Cohen, Aaron J; Singer, Burton H
Abstract : Background: Monitoring and empirical evaluation are essential components of evidence based public health policies and programmes. Consequently, there is a growing interest in monitoring of, and indicators for, major environmental health risks, particularly in the developing world. Current large scale data collection efforts are generally disconnected from micro-scale studies in health sciences, which in turn have insufficiently investigated the behavioural and socioeconomic factors that influence exposure. Study design: A basic framework is proposed for development of indicators of exposure to environmental health risks that would facilitate the (a) assessment of the health effects of risk factors, (b) design and evaluation of interventions and programmes to deliver the interventions, and (c) appraisal and quantification of inequalities in health effects of risk factors, and benefits of intervention programmes and policies. Specific emphasis is put on the features of environmental risks that should guide the choice of indicators, in particular the interactions of technology, the environment, and human behaviour in determining exposure. The indicators are divided into four categories: (a) access and infrastructure, (b) technology, (c) agents and vectors, and (d) behaviour. The study used water and sanitation, indoor air pollution from solid fuels, urban ambient air pollution, and malaria as illustrative examples for this framework. Conclusions: Organised and systematic indicator selection and monitoring can provide an evidence base for design and implementation of more effective and equitable technological interventions, delivery programmes, and policies for environmental health risks in resource poor settings.